2010
DOI: 10.1097/ccm.0b013e3181d9db8c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective decontamination of the digestive tract on multiple organ dysfunction syndrome: Systematic review of randomized controlled trials*

Abstract: Selective decontamination of the digestive tract reduces the number of patients with multiple organ dysfunction syndrome. Mortality was not significantly reduced, probably because of the small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…Indeed, past studies have shown that selective gut decontamination may reduce severe infections, incidence of multiple-organ dysfunction syndrome, and may lower the risk of acute GVHD. [64][65][66][67][68][69][70] Interestingly, both of our two prophylactic protocols seemed to be equally effective in terms of reducing BSIs. However, an incidental, but possibly important finding was the increase in resistant GNB to potent antibiotics that are commonly used in the treatment of febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past studies have shown that selective gut decontamination may reduce severe infections, incidence of multiple-organ dysfunction syndrome, and may lower the risk of acute GVHD. [64][65][66][67][68][69][70] Interestingly, both of our two prophylactic protocols seemed to be equally effective in terms of reducing BSIs. However, an incidental, but possibly important finding was the increase in resistant GNB to potent antibiotics that are commonly used in the treatment of febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…, Sadfar et al (10) and Silvestri et al (16) showed an impact on mortality. However, due to small sample size, the differences were not significant.…”
Section: Luciano Silvestrimentioning
confidence: 95%
“…shown to reduce hospital acquired infection rates and mortality in critically ill patients [5][6][7] .…”
Section: Selective Decontamination Of the Digestive Tract (Sdd) Is Anmentioning
confidence: 99%
“…Despite considerable evidence supporting the benefit of SDD [5][6][7] , adoption internationally is low 9,10 . Amongst proposed reasons for this lack of adoption are controversies surrounding prophylactic use of antibiotics and associated risk of antibiotic resistance 11,12 and purported difficulty of SDD implementation and delivery 13 .…”
Section: Selective Decontamination Of the Digestive Tract (Sdd) Is Anmentioning
confidence: 99%